A success story: identified gaps and the way forward for low HIV prevalence in Bangladesh - Kamar Rezwan; Hussain Sarwar Khan; Tasnim Azim; Razia Pendse; Swarup Sarkar; N. Kumarasamy (Elsevier, 2016)
Bangladesh remains a low prevalence country for HIV infection. In this article we attempt to address the reasons for the present success in this country and the challenges lying ahead to minimise the spread of HIV in the future.